2012
DOI: 10.5194/acp-12-8851-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stratospheric NO<sub>2</sub> trends above Jungfraujoch using ground-based UV-visible, FTIR, and satellite nadir observations

Abstract: Abstract. The trend in stratospheric NO 2 column at the NDACC (Network for the Detection of Atmospheric Composition Change) station of Jungfraujoch (46.5 • N, 8.0 • E) is assessed using ground-based FTIR and zenith-scattered visible sunlight SAOZ measurements over the period 1990 to 2009 as well as a composite satellite nadir data set constructed from ERS-2/GOME, ENVISAT/SCIAMACHY, and METOP-A/GOME-2 observations over the 1996-2009 period. To calculate the trends, a linear least squares regression model includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 39 publications
4
39
1
Order By: Relevance
“…This formula has previously been used for trends in NO 2 (Van der A et al, 2006(Van der A et al, , 2008Hendrick et al, 2012).…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This formula has previously been used for trends in NO 2 (Van der A et al, 2006(Van der A et al, , 2008Hendrick et al, 2012).…”
Section: Multiple Regression and Proxiesmentioning
confidence: 99%
“…Such models have been extensively used in recent years to infer trends in long-term atmospheric time series of groundbased instruments; in particular, they have been used to study the evolution of stratospheric ozone (Bodeker et al, 1998;Wohltmann et al, 2007;Fioletov, 2008;Mäder et al, 2010), NO 2 ( Van der A et al, 2006Van der A et al, , 2008Gruzdev, 2009;Hendrick et al, 2012) and other species (i.e. Remsberg, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A positive trend was found over the middle latitudes of the Southern Hemisphere, in good agreement with expectations, whereas the trend over the Northern Hemisphere was negative, in disagreement with the increase of emissions of nitrous oxide (N 2 O), which is a precursor of NO 2 . Hendrick et al (2012) also found negative trends over Jungfraujoch for the period 1990-2009. Gil-Ojeda et al (2015) found a hemispherical and latitude dependence on the sign and magnitude of the trend based on four GB DOAS stations.…”
Section: Introductionmentioning
confidence: 85%
“…Large differences in AVK profiles between DOAS, FTIR and satellite techniques would lead to uncertainties difficult to quantify and could result in a more complicated intercomparison (Adams et al, 2012;Dirksen et al, 2011;Hendrick et al, 2012;Peters et al, 2012;Sussmann et al, 2005, among others). This, however, is not the case.…”
Section: Comparison Methodologymentioning
confidence: 99%
See 1 more Smart Citation